Outcomes of Pharmaceutical Care in Patients with New Smear Pulmonary Tuberculosis at Uttaradit Hospital - Kantared, Mantana (Health Science Clinical Research, 2020)
Introduction : According to the treatment of tuberculosis has been multiple medication and the period of time more than 6 months, the drug related problems will be presents. Pharmaceutical care is the responsible provision of pharmacy to preventing and reduce drug related problems. Objective : The comparation of the pharmaceutical outcomes between patients with new smear pulmonary tuberculosis whom received pharmaceutical care intervention and standard treatment. Methods : Intervention research with historical controlled at Uttaradit Hospital. There were 73 patients in the study, divided in two groups. The intervention group were 29 patients, prospective data collection between December 2019 to September 2020. The control group with 44 patients that were collected the data retrospectively from their medication record between October 2018 to September 2019. Drug related problems, adverse drug reactions, medication adherence and clinical outcome were evaluated. Statistic analysis were performed by chi-squared test and fisher’s exact test with significant at 0.05. Results : The proportion of subjects in intervention group have sputum convert at the end of second month was 72.4 and treatment outcomes was 93.1 which higher than the control group (p=0.124) and (p=0.696) respectively. The proportion of medication adherence in intervention group was 93.1 and the control group was 72.7 (p<0.05). Drug related problems in intervention group were less (p<0.05) so that was 1.93±1.28 and 2.66±1.63 respectively. Adverse drug reactions were the most of drug related problems. Conclusions : Pharmaceutical care interventions can be made to improve with the medication adherence and reduce drug related problems in order to increase treatment outcomes. The most prevalent drug related problems were adverse drug reactions and inappropriate dosage of anti-tuberculosis drugs. Role of pharmacist in pulmonary tuberculosis must be contribute in the first diagnosis, especially in patients with renal function impairment. Keywords : Pharmaceutical care, pulmonary tuberculosis, drug related problems